Standardizing tooth size discrepancies in orthodontic patients - Llavore, Lotus D. (The Journal of the Philippine Dental Association)
The Bolton analysis, based on interarch ratios, remains the most recognized and widely used method for detecting tooth size discrepancies. Bolton ratios of 135 patients accepted for treatment in an orthodontic program were evaluated in the present study to determine the prevalence of significant tooth size discrepancies in clinical practice. A clinically significant tooth size discrepancy was denoted as one whose value was outside of the 2 standard deviations from Bolton's means. The results showed that for each of the malocclusion groups, both the overall and anterior ratios were higher in the Class III malocclusion group than in the Class I malocclusion group, and the Class I group tend to have higher mean values than the Class II malocclusion group. Compared to Bolton's original sample, the mean tooth size ratios for the orthodontic patients of the present study were slightly higher than Bolton's values and had a larger range than his sample. The impaired t-test showed that there was no significant sexual dimorphism for any of the parameters for the three malocclusion groups (p>0.05). The chi-square test showed that there were no significant differences in the overall ratio among the three malocclusion groups (p>0.05) and that only 8.15% (11 out of 135) of the total population presented with clinically significant tooth size discrepancies in the overall ratio. Likewise, for the anterior ratio, the chi-square test showed that there were no significant differences among the three malocclusion groups (p>0.05) although a larger percentage of 25.93% (35 out of 135) of the total population presented with clinically significant tooth size discrepancies in the anterior ratio. The results of the chi-square test also showed no significant difference in the prevalence of clinically significant discrepancies between genders for both the tooth size ratios (p>0.05).